Ground Demonstration of the Use of Limnospira indica for Air Revitalization in a Bioregenerative Life-Support System Setup: Effect of Non-Nitrified Urine–Derived Nitrogen Sources - Sachdeva, Neha; Poughon, Laurent; Gerbi, Olivier; Dussap, Claude-Gilles; Lasseur, Christophe; Leroy, Baptiste; Wattiez, Ruddy (Frontiers in Astronomy and Space Sciences, 2021)
Long-duration human space-missions require considerable amounts of water, oxygen and nutritious biomass. Additionally, the space-vehicles must be well-equipped to deal with metabolic human-waste. It is therefore important to develop life-support system which make these missions self-sufficient in terms of water, food and oxygen production as well as waste management. One such solution is the employment of regenerative life-support systems that use biological and chemical/physical processes to recycle crew-waste, revitalize air and produce water and food. Photosynthetic cyanobacteria Limnospira could play a significant role meeting these objectives. Limnospira can metabolize CO2 and nitrogen-rich human-waste to produce oxygen and edible biomass. So far, life-support system studies have mainly focused on using chemical/physical methods to recycle water, degrade human-waste and recycle CO2 to oxygen. Nowadays, additional microbial processes are considered, such as nitrification of urea-ammonium rich human-waste and then use the nitrate for cyanobacterial cultivation and air-vitalization. This cascade of multiple processes tends to increase the complexity of the life-support systems. The possibility to use non-nitrified urine for Limnospira cultivation can partially solve these issues. Our previous studies have shown that it is possible to cultivate Limnospira with urea and ammonium; the prominent nitrogen-forms present in non-nitrified urine. In this study, we investigated the possibility to cultivate Limnospira with the different nitrogen-forms present in non-nitrified urine and also evaluated their effect on the oxygen production capacity of Limnospira. For this 35-days long study we worked on a simplified version of European Space Agency’s MELiSSA. During this ground-demonstration study, we monitored the effect of urea and ammonium (vs nitrate) on the oxygen production capacity of Limnospira. A deterministic control law, developed and validated on the basis of a stochastic light-transfer model, modulated (increase/decrease) the incident light on the photobioreactor (with Limnospira) to control oxygen levels in the closed loop. The CO2 from mouse compartment was recycled as carbon-source for Limnospira. We observed that while the system could meet the desired oxygen levels of 20.3% under nitrate and urea regime, it could only reach a maximum O2 level of 19.5% under ammonium regime.